2011
DOI: 10.1016/j.jprot.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the iron response in Acinetobacter baumannii: A proteomics approach

Abstract: Iron is an essential nutrient that plays a role in bacterial differential gene expression and protein production. Accordingly, the comparative analysis of total lysate and outer membrane fractions isolated from A. baumannii ATCC 19606 T cells cultured under iron-rich and -chelated conditions using 2-D gel electrophoresis-mass spectrometry resulted in the identification of 58 protein spots differentially produced. While 19 and 35 of them represent iron-repressed and iron-induced protein spots, respectively, fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 57 publications
4
92
0
1
Order By: Relevance
“…The biological relevance of this observation is not clear considering that the binding of SecA to the L23 ribosomal protein seems to be the only interaction between this protein and the ribosome that has been described (68). Equally unclear is the apparent association of ribosomal proteins with the outer membrane fraction, a phenomenon we believe is not due solely to fraction contamination since we did not observe it when we used the same experimental approach to study the effect of iron on protein synthesis in the same A. baumannii strain (41). Taken together, our results indicate that although the interruption of the 3= end of secA in A. baumannii ATCC 19606 T is not lethal, it results in a protein homeostatic response to protect cells from different stressors that otherwise could negatively affect overall bacterial viability.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…The biological relevance of this observation is not clear considering that the binding of SecA to the L23 ribosomal protein seems to be the only interaction between this protein and the ribosome that has been described (68). Equally unclear is the apparent association of ribosomal proteins with the outer membrane fraction, a phenomenon we believe is not due solely to fraction contamination since we did not observe it when we used the same experimental approach to study the effect of iron on protein synthesis in the same A. baumannii strain (41). Taken together, our results indicate that although the interruption of the 3= end of secA in A. baumannii ATCC 19606 T is not lethal, it results in a protein homeostatic response to protect cells from different stressors that otherwise could negatively affect overall bacterial viability.…”
Section: Discussionmentioning
confidence: 83%
“…Considering the role SecA plays in the translocation of different proteins, we examined differences in protein production between the ATCC 19606 T parental strain and the isogenic 2010 secA insertion derivative using the 2-DE mass spectrometry approach that we applied to study the effect of iron on protein production in this pathogen (41). This proteomics study identified 35 protein spots, which represent 27 different proteins that were underproduced or not produced in the 2010 mutant compared with the parental strain (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations